An Enhanced and Secure Approach of Load Balancing in Cloud Computing - Gupta, Ruhi; Bhatia, Rekha (International Journal of Computer Sciences and Engineering, 2014)
The load balancing problem is the most divergent job to be achieved while dealing with Cloud Computing. Along with load balancing accomplishment, various access Control mechanisms are to be forked with. DAC, MAC,RBAC are such access controls that have already been developed. But as the number of clients are trafficking the network, so do the problems. This paper deals with all such problems which are posing a great threat to the users while accessing the internet. It does all this by checking the specifications of virtual machines by the use of surveys. It will help in saving time as well as cost factor.